Degradation Resistance and Reliability Analysis of Recycled Aggregate Concrete in a Sulfate Environment - Hui Cao; Lifeng Zhao; Chenggong Lu; Lijuan Guan; Hongxia Qiao; Qiong Li (Advances in Materials Science and Engineering)
Resistance to sulfate degradation is an important index used to measure concrete’s durability. In this study, recycled aggregate concrete (RAC) with a 0%, 30%, and 50% recycled coarse aggregate substitution rate and a 0% and 15% recycled fine aggregate replacement rate was used as the research object, and its degradation resistance was evaluated by the mass loss rate and the relative dynamic modulus of elasticity. The degradation products were studied and analyzed with SEM scanning electron microscopy and XRD phase analysis. The relative dynamic modulus of elasticity was selected as the degradation index, the RAC concrete’s degradation resistance was modeled by Wiener, and the reliability curve was obtained. The results showed that expansion products, such as gypsum and Ettringite, were produced in RAC concrete in a dry-wet sulfate cycling environment, and such defects as pores and voids were filled in the initial stage. The stress the expansion products exerted in the later stage caused the concrete to crack and peel, which demonstrated that the fluctuation law of mass and the dynamic elastic modulus increased first and then decreased. The recycled coarse aggregate substitution ratio’s effect on RAC concrete is higher than that of recycled fine aggregate. The reliability curve established by the Wiener model can reflect the reliability of RAC concrete under different cycles well and can obtain RAC concrete’s sulfate degradation resistance life with different aggregate substitution rates.